Building Information Modeling (BIM) as Tool to Develop Solution for Bridge Rehabilitation - Pratiksha B. Vanjari; Sushma S. Kulkarni (Universitas Pendidikan Indonesia (UPI), 2022)
Building Information Modeling (BIM) consists of processes that produce and handle information during the life cycle of a building. BIM may also be a technique involving the development and management of digital representations of a building or facility’s physical and useful features. In 2D BIM software package programs, the paper explains the three-dimensional (3D) modeling of the project and the multidimensional (4D) modeling using another BIM viewer. Revit model is created based on primary data that visualizes the bridge. For analysis, dead load and moving load are considered. From the result analysis of the structure, an approach is provided to repair the Bridge using BIM. As per IRC: SP -40 (Guidelines for techniques for strengthening and rehabilitation of bridges). This paper is an attempt to build a model that could demonstrate the use of BIM for bridge rehabilitation.